IOT Controlled Water Trash Collector Boat - Shikhar Shukla; Aman Chauhan; Sonal Singh; Mr. Kamaleshwar Dhar Dwivedi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The escalating issue of surface waste pollution in rivers presents a significant threat to environmental health and ecological balance, particularly in urban centers like Lucknow, Uttar Pradesh, India. This report introduces a conceptual design for an automated trash collector boat employing a conveyor belt mechanism for the efficient removal of floating debris from the surface of rivers. Driven by the urgent need for effective and sustainable solutions to mitigate river pollution and its detrimental impacts on the local ecosystem and community, this project proposes a boat that can be remotely operated and controlled via mobile Wi-Fi. The report outlines the proposed design, detailing the conveyor belt-based collection system, onboard storage, and propulsion method, along with the integration of a mobile Wi-Fi control system for autonomous or semi-autonomous operation. It further discusses the anticipated benefits of such a vessel in enhancing river cleanliness, potential challenges in its development and deployment, and directions for future work, including detailed engineering, prototyping, and software development for the control system. This preliminary investigation highlights the potential of an automated trash collector boat with mobile Wi-Fi control to significantly contribute to cleaner and healthier river environments in Lucknow and similar urban settings.
Keywords: River pollution; Automated trash collector boat; Floating debris removal; Mobile Wi-Fi control; Autonomous operation; Environmental health; Sustainable solutions; River cleanliness